Errors in Family Practice - Pierre de Villiers (South African Family Practice)
We read about doctors' errors in the newspapers almost on a daily basis. Rightly so one may add, because doctors are dealing with human lives and their errors may be costly in terms of suffering and even loss of life. Society places a heavy demand on doctors. If engineers can place a man on the moon, and doctors do organ transplants as a matter of routine and provide new miracle cures for formerly incurable diseases, then errors are seemingly becoming inexcusable.